Mídia e abuso sexual nos esports: construções de discurso no jornalismo de videogames brasileiro - Medeiros, Kennet Anderson da Cruz (2024)
This work carries out a discourse analysis of news stories dealing with accusations of sexual abuse against "MiT", an influential figure in the Brazilian esports scene. It seeks to understand how a media outlet specializing in video games, and especially competitive electronic games, produces meanings about this event. In addition to studying what kinds of meanings these are, the research focuses its analysis on identifying linguistic mechanisms that elicit ideological formations from this press. Considering that the journalistic media have ways of influencing the public debate, the objective is to understand how an opportune topic to discuss gender violence is conveyed to the video game consumer public.With this in mind, we set out with the following research problem: based on which discursive practices does contemporary Brazilian video game journalism construct news about sexual abuse in esports? In order to arrive at this answer, the work is divided into four chapters. In the first, we produce a literature review that explores the relationship between the press and the video games industry, the gaming press and gender issues, and the esports scene. Then, in chapter 2, we present the discourse theory that will serve as the theorical-methodologic basis. We focus mainly on the influences of Foucault (2008) and Pêcheux (1997a, 1997b) on discourse analysis in the French tradition. From these influences, we draw on Charaudeau's (2005, 2013) semiolinguistic approaches to analyzing informative discourse as a methodological contribution. Chapter 3 discusses the corpus to be analyzed: 10 news stories, out of a total of 39 identified, which deal with allegations of sexual abuse in the Brazilian esports scene between January 5 and 9, 2021. Produced by 5 Brazilian websites (Globo Esporte, ESPN, Mais Esports, The Enemy and MGG), the news items were standardized and processed using Iramuteq, a textual data analysis software. Finally, the data is categorized based on Charaudeau's (2005, 2013) semiolinguistics and discussed in Chapter 4. In order to answer the research problem, the results point to: (1) the use of processes of social qualification (through professional history) and naming (through nicknames) to construct affective meanings; (2) the use of paraphrases, confrontations of speeches, and sources to generate effects of truth on material meanings constructed from ideological formations; (3) the use of argumentative processes that materialize in victim-blaming devices; (4) the use of narrative processes that moralize violence, but refrain from problematizing it.